2011
DOI: 10.1097/gme.0b013e31821adb43
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive risk factors for cardiovascular disease mortality among postmenopausal women in Korea

Abstract: An inverse relationship between age at first childbirth and the risk of cardiovascular disease mortality exists. In addition, early menarche may be a reproductive risk factor for coronary heart disease mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
62
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 46 publications
10
62
1
1
Order By: Relevance
“…Some, but not all, have reported that early age at menarche was associated with increased risk of coronary heart disease incidence 5,6 or mortality. [7][8][9][10][11] Consistent with these reports, we found that early age at menarche was associated with increased risk of incident coronary heart disease. Although others have reported an increased coronary disease risk with early menarche among nonsmokers only, 9-11 we found similar associations among smokers and nonsmokers alike.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Some, but not all, have reported that early age at menarche was associated with increased risk of coronary heart disease incidence 5,6 or mortality. [7][8][9][10][11] Consistent with these reports, we found that early age at menarche was associated with increased risk of incident coronary heart disease. Although others have reported an increased coronary disease risk with early menarche among nonsmokers only, 9-11 we found similar associations among smokers and nonsmokers alike.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have investigated the association of menarcheal age with cerebrovascular disease (Table VII in the online-only Data Supplement). Most of these studies reported no significant relationship between cerebrovascular disease risk and age at menarche, 6,[8][9][10][11]13 with only 1 study suggesting an increased risk of cerebrovascular disease associated with early menarche. 7 In our cohort, we found a significant increase in cerebrovascular disease risk not only with early (≤10 years) but also with late (≥17 years) menarche.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La menarquia temprana es un factor de riesgo para algunos tipos de cáncer y otras enfermedades crónicas no transmisibles [15][16][17][18] , por lo que debiera constituir una preocupación en salud pública. Por otro lado, la menarquia temprana se asocia con sobrepeso en período pre-puberal y, también en el período de la adolescencia y adultez, aunque esta última asociación es controversial [19][20][21] .…”
unclassified
“…For women, most studies find a negative association between age at first birth (often defined categorically as 'on time' vs 'early' first birth) and mortality risk (Doblhammer 2000;Grundy 2009;Grundy & Kravdal 2008;Grundy & Tomassini 2005). This relationship has been reported also for cardiovascular disease mortality (Chang et al 2011), diabetes related mortality (Vandenheede et al 2012), and various other causes of death (Grundy & Kravdal 2010). Mirowsky (2002Mirowsky ( , 2005 finds an 'optimal' age at first birth for women's health in the early-thirties, and a negative linear relationship between age at first birth and mortality risk.…”
Section: Fertility History and Healthmentioning
confidence: 99%